Abstract Data Interpolation in Library OPAC: from the Perspective of Information Dissemination - Dian Kristyanto (Program Studi Ilmu Perpustakaan UIN Alauddin, 2022)
OPAC libraries basically have provided complete metadata with various data fields that can be used to contain more detailed collection information. This paper will analyze the potential for additional data collections, especially collection abstractions from the point of view of information needs and information dissemination. The study used a literature review analysis by referring to several sources of information such as scientific articles from electronic journals or other online sources as well as books relevant to this study. The data was obtained by observing the OPAC of online-based libraries from several educational institutions. The results of the study showed that the metadata pattern built by the library is still limited to a brief description of the collection so that the benefits of the information are not necessarily obtained by the user. The addition of abstract data to the OPAC, from the point of view of information dissemination is very necessary because the users need more detailed information. Libraries can add abstract data by choosing one of the methods in the summary process, namely abstraction and extraction.